REVIEW OF FERMION HAMILTONIAN IN BOZON SPACE - Baktybayev К.B.; Koilyk N.О.; Ramankulov К.Е. (Recent Contributions to Physics, 2008)
Fermion theory was represented into boson’s space by Daison, Belev-Zelevinski and Seniority methods. It was shown that FDSM and its boson representation gave a good explanation of experimental data. So it was shown that from the Hamiltonian of FDSM could be constructed boson type IBM-Hamiltonian by representation. So fermion theory gives microscopically base of phenomenological approaches.